The pharmacokinetics of transdermal flunixin meglumine in Holstein calves. Issue 6 (28th April 2016) - Kleinhenz, M. D.; Van Engen, N. K.; Gorden, P. J.; KuKanich, B.; Rajewski, S. M.; Walsh, P.; Coetzee, J. F.
Abstract : This study describes the pharmacokinetics of topical and intravenous (IV) flunixin meglumine in Holstein calves. Eight male Holsteins calves, aged 6 to 8 weeks, were administered flunixin at a dose of 2.2 mg/kg intravenously. Following a 10‐day washout period, calves were dosed with flunixin at 3.33 mg/kg topically (transdermal). Blood samples were collected at predetermined times from 0 to 48 h for the intravenous portions and 0 to 72 h following topical dosing. Plasma drug concentrations were determined using liquid chromatography with mass spectroscopy. Pharmacokinetic analysis was completed using noncompartmental methods. The mean bioavailability of topical flunixin was calculated to be 48%. The mean AUC for flunixin was determined to be 13.9 h × ug/mL for IV administration and 10.1 h × ug/mL for topical administration. The mean half‐life for topical flunixin was 6.42 h and 4.99 h for the intravenous route. The Cmax following topical application of flunixin was 1.17 μg/mL. The time to maximum concentration was 2.14 h. Mean residence time (MRT) following IV injection was 4.38 h and 8.36 h after topical administration. In conclusion, flunixin when administered as a topical preparation is rapidly absorbed and has longer half‐life compared to IV administration.